2020
DOI: 10.1002/cam4.3587
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of drugs affecting hypertension in bevacizumab‐treated patients and examination of the impact on the therapeutic effect

Abstract: Background In patients treated with bevacizumab, hypertension may be a biomarker of therapeutic efficacy. However, it is not clear whether drugs that control blood pressure influence bevacizumab's efficacy. In this study, we investigated drugs that may affect hypertension in bevacizumab‐treated patients and examined the impact on the therapeutic effect. Patients and methods We analyzed 3,724,555 reports from the third quarter of 2010 to the second quarter of 2015. All data were obtained from the Food and Drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This is because NSAID-induced gastric damage is known to include acid-dependent lesions, and because omeprazole inhibits gastric acid secretion through suppression of H+/K+ ATPase in the parietal cells [ 51 ]. Moreover, a previous study also showed an omeprazole-like proton pump inhibitor (PPI) [ 52 ] induced the VEGFA expression [ 53 ]. Similar findings regarding MDA, GSH, SOD, and CAT levels were also found in previous rat studies [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because NSAID-induced gastric damage is known to include acid-dependent lesions, and because omeprazole inhibits gastric acid secretion through suppression of H+/K+ ATPase in the parietal cells [ 51 ]. Moreover, a previous study also showed an omeprazole-like proton pump inhibitor (PPI) [ 52 ] induced the VEGFA expression [ 53 ]. Similar findings regarding MDA, GSH, SOD, and CAT levels were also found in previous rat studies [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of vonoprazan on VEGF expression was evaluated using the same colorectal cancer cell line as in a previous study (Yagi et al, 2021). The results showed that vonoprazan does not upregulate VEGF expression at the gene and protein levels, whereas PPI does.…”
Section: Discussionmentioning
confidence: 99%
“…The second approach was used for bevacizumab-induced hypertension ( Yagi et al, 2021 ). Hypertension is a frequent adverse event in bevacizumab-treated patients, and the development of hypertension has been suggested to be a biomarker of treatment response; FAERS found that hypertension was less frequently reported in bevacizumab-treated patients who were using omeprazole.…”
Section: Example Of Actual Research: Approach To Drug-induced Adverse Eventmentioning
confidence: 99%